2019
DOI: 10.3390/ijerph16132286
|View full text |Cite
|
Sign up to set email alerts
|

How do Interpersonal Relationships Relieve Adolescents’ Problematic Mobile Phone Use? The Roles of Loneliness and Motivation to Use Mobile Phones

Abstract: The current study aimed to explore the underlying mechanisms of how interpersonal relationships relieve adolescents’ problematic mobile phone use (PMPU) and to examine the potential mediating roles of loneliness and motivation to use mobile phones. Four thousand five hundred and nine middle school students from four provinces in China were recruited to participate in the investigation. The results showed that the parent–child relationship but not the teacher–student relationship, had a direct and negative effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 50 publications
(73 reference statements)
4
34
0
2
Order By: Relevance
“…In addition, lonely adolescents tend to prefer online communication and are more likely to use the internet as a coping strategy for stressful relationships leading to more PIU [ 45 ]. Similarly, recent research has shown that negative teacher-student relationships have an indirect effect on problematic mobile phone use through loneliness and motivation to escape negative emotions [ 46 ]. Conversely, it is likely that PIU may also have detrimental effects upon interpersonal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lonely adolescents tend to prefer online communication and are more likely to use the internet as a coping strategy for stressful relationships leading to more PIU [ 45 ]. Similarly, recent research has shown that negative teacher-student relationships have an indirect effect on problematic mobile phone use through loneliness and motivation to escape negative emotions [ 46 ]. Conversely, it is likely that PIU may also have detrimental effects upon interpersonal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, face-to-face communication with others may bring additional pressures to them. This may encourage a reliance on mobile phones as a form of escape and compensation for their interpersonal communication in the real world ( Zhen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the speed of access to psychological help with the help of mobile devices was considered earlier, but rarely in the context of helping teenagers. Scientists often proceeded from the fact that adolescents most of the time are under the care and supervision of either teachers or parents, therefore psychological assistance is largely the responsibility of these categories of persons [28]. The ever deeper penetration of the digital environment in particular, and into human family relations, leads to the fact that the online and mobile life of adolescents is rarely completely controllable and can itself provoke negative behavioral changes [29].…”
Section: Discussionmentioning
confidence: 99%